The reinforcement and healing of asphalt mastic mixtures by rejuvenator encapsulation in alginate compartmented fibres. (15th July 2016) - Tabaković, A; Post, W; Cantero, D; Copuroglu, O; Garcia, S J; Schlangen, E
Abstract: This paper explores the potential use of compartmented alginate fibres as a new method of incorporating rejuvenators into asphalt pavement mixtures. The compartmented fibres are employed to locally distribute the rejuvenator and to overcome the problems associated with spherical capsules and hollow fibres. The work presents proof of concept of the encapsulation process which involved embedding the fibres into the asphalt mastic mixture and the survival rate of fibres in the asphalt mixture. To prove the effectiveness of the alginate as a rejuvenator encapsulating material and to demonstrate its ability survive asphalt production process, the fibres containing the rejuvenator were prepared and subjected to thermogravimetric analysis and uniaxial tensile test. The test results demonstrated that fibres have suitable thermal and mechanical strength to survive the asphalt mixing and compaction process. The CT scan of an asphalt mortar mix containing fibres demonstrated that fibres are present in the mix in their full length, undamaged, providing confirmation that the fibres survived the asphalt production process. In order to investigate the fibres physiological properties and ability to release the rejuvenator into cracks in the asphalt mastic, the environmental scanning electron microscope and optical microscope analysis were employed. To prove its success as an asphalt healing system, compartmented alginate fibres containing rejuvenator were embedded in asphalt mastic mix. The three point bend tests were performed on the asphalt mastic test samples and the degree to which the samples began to self-heal in response was measured and quantified. The research findings indicate that alginate fibres present a promising new approach for the development of self-healing asphalt pavement systems.